Intraspecific structure of the Coregonus lavaretus complex in water bodies of Siberia: a case of postglacial allopatric origin of Yukagirian whitefish - Bochkarev, Nickolay A.; Zuykova, Elena I.; Pestryakova, Lyudmila A.; Ushnitskaya, Lena A.; Zakharov, Evgeny S.; Politov, Dmitry V.; Andree, Karl B.; Solovyev, Mikhail M. (Canadian Journal of Zoology, 2021)
The results of morphological and genetic analyses of forms/species of the Coregonus lavaretus pidschian (Gmelin, 1789) complex from the Indigirka and Kolyma river basins are presented in the context of there being recent postglacial speciation events. It has been found that the studied whitefishes belong to the sparsely rakered and low lateral-line forms and have previously been described as Coregonus lavaretus pidschian n. jucagiricus Drjagin (Berg), 1932. Based on these characters, this whitefish does not differ from most Arctic whitefish populations (in particular from Coregonus lavaretus glacialis Kirillov, 1972). Analysis of variability of the ND1 gene (mtDNA) showed that whitefishes from the Indigirka and Kolyma basins belong to a distant phylogenetic lineage, which is significantly different from all previously studied whitefish lineages from the Ob, Yenisei, Lena, Anadyr, and Amur river basins. Analysis of variability of the ITS1 fragment (nDNA) showed that all studied forms/species (from Ob River to Amur River basins), including C. l. pidschian n. jucagiricus, have a tandem arrangement of two identical nucleotide fragments and very similar nucleotide composition of the ITS1 region. Based on contemporary data, this phylogenetic lineage of the C. pidschian complex could be considered a young postglacial allopatric species.